Carbon encounters: cognizing the calculus of climate change - Battle, Angela (My University, 2016)
Governments, like South Africa, are implementing carbon tax and carbon credit programs to incent businesses to lower their GHG emissions. That is not to say there are not loftier motivations in the wider world, but in this study we have mostly encountered Homo Economicus. Our observations have noted that people either want to make money or save money by way of participating in the green economy. Earth’s threatening posture is yet to change our “habitus”. The changes so far are from economic coercion and not ecological conviction. And it’s primarily prompted through the scientific community, who are understandably, the first responders to a threat with slow and mostly imperceptible reverberations. The responses of those trying to make money, involve participating in the process of carbon commodification. CERs are a new form of currency available to those able to deploy labor and capital in efforts to capture carbon molecules and prevent their creation. The looming South African carbon tax has spurred organizations to lower their emissions so as not to effect bottom-line profitability. [Taken from the conclusion. No abstract provided]
Thesis (M.A. (Anthropology))--University of the Witwatersrand, Faculty of Humanities, School of Social Sciences, 2016.
Keywords: Climatic changes--Environmental aspects--South Africa; Carbon taxes--South Africa; Carbon dioxide--Environmental aspects